Dialectics politeness realization acts of guidance and counseling: study psychopragmatics - Kusmanto, Hari (Konselor, 2019)
This study aims to identify a form of politeness in the dialectic of guidance and counseling. The data in this study is a word, phrase, sentence, and discourse Obtained through listening process guidance and counseling services. This research of the data sources conversation in the process of guidance and counseling services. The research use the data collection methods of documentation, see and continued with the technical note. Use research the method of data analysis and the pragmatic intralingual match. The results Showed a form of politeness in the dialectic of guidance and counseling services include: (1) a greeting; (2) use the expression preamble; (3) use of humor; (4) use good language or not hurt the hearer; and (5) to give a compliment.Â